Seaport positioning supported by the combination of some quantitative and qualitative approaches - Bauk, Sanja; Šekularac-Ivošević, Senka; Jolić, Natalija (Transport, 2015)
The ports’ management is facing the challenge of sustainable port development, considering several aspects: economic, technological, logistical, environmental, and community involvement. Although the numerous scientific concepts have been developed for explaining the trends of ports’ involvement into the logistics chains, this research work presents an attempt to draw the attention to the marketing aspect of the port mission, being focused primarily on the customers’ needs, whose preferences are the key factor in selecting specific port in competitive environment. Therefore, the Adriatic, Aegean, and Black Sea ports, sharing the unique marketing features and target market, have been analyzed with the aim to be mutually positioned. The considered ports have similar goals: to achieve the greater degree of competitiveness as well as to acquire the larger number of customers being attracted on the basis of superior port choice criteria. These circumstances have been explored through some distinctive quantitative and qualitative criteria by employing the appropriate, well known and structured quantitative PROMETHEE and AHP method. The obtained results are presented by perception maps, and described on the basis of gained quantitative indicators and the qualitative explanations given by the authors, primarily, in the marketing manner.First published online: 25 Oct 2013